The Emerging Role of Hedgehog Signaling in Viral Infections - Zhou, Yulin; Huang, Jinhua; Jin, Boxin; He, Su; Dang, Yongfang; Zhao, Tiejun; Jin, Zhigang (Frontiers in Microbiology, 2022)
The hedgehog (HH) signaling pathway is one of key pathways that are indispensible for many developmental processes and postnatal tissue homeostasis. Dysregulated HH signaling could lead to developmental disorders and tumorigenesis in a variety of tissues via inherited or sporadic mutation, gene overexpression and crosstalk with other signaling pathways. Recently, accumulating evidence has showed that HH signaling is targeted by viruses to facilitate viral transcription, immune evasion and uncontrolled growth, leading to effective viral replication and pathogenesis. Here we will summarize recent advances in functional interaction between HH signaling and different types of viruses, particularly focusing on the pathological role of HH signaling in viral infections and related diseases.